Case Report: Durvalumab-Associated Encephalitis in Extensive-Stage Small Cell Lung Carcinoma - Shionoya, Yosuke; Hattori, Akito; Hanada, Taro; Fujino, Michihiro (Frontiers in Oncology, 2021)
In recent years, the clinical importance of immunotherapy has been demonstrated in the treatment of extensive-stage small-cell lung cancer (ES-SCLC). However, immune checkpoint inhibitors (ICIs) have been shown to cause immune-related adverse events (irAEs), including autoimmune encephalitis. Here, we describe the treatment of a patient with ES-SCLC who developed immune-related encephalitis. A 68-year-old Japanese woman with ES-SCLC treated with carboplatin plus etoposide plus durvalumab 20 days earlier was admitted to our hospital with a high fever and anorexia. Her symptoms gradually worsened over time, and she had a headache daily and showed reduced levels of consciousness. An electroencephalogram showed diffuse slow waves, and there was a slight increase in cell counts and an increase in protein levels in the cerebrospinal fluid. The patient was diagnosed with durvalumab-associated encephalitis. Her symptoms improved immediately after steroid pulse therapy. Following steroid pulse therapy, oral prednisolone (1 mg/kg) was administered, and then, the dose was gradually reduced. Subsequently, treatment with carboplatin plus etoposide without durvalumab was restarted. In conclusion, this study shows the efficacy of steroid therapy in the treatment of durvalumab-induced encephalitis in ES-SCLC.